The complete guide to portfolio construction and management - Snopek, Lukasz (Chichester, West Sussex : John Wiley & Sons, 2012)
'The Complete Guide to Portfolio Construction and Management is a one-stop guide to portfolio construction and management in a modern context'--
Includes bibliographical references and index.
Keywords: Portfolio management